Internet asset securitization resource integration system - SHAO YUJUN (2015)
The invention discloses an Internet asset securitization resource integration system. The objective of the invention is to solve the problems of unsmooth financing channels, insufficient capital sources and simple and traditional financing tools existing on enterprises at present. The Internet asset securitization resource integration system includes a sponsor, an underlying asset pool, a special purpose vehicle (SPV), a credit increasing mechanism, a credit rating mechanism, a management mechanism, a trustee mechanism, a underwriter and an investor module; each module includes a plurality of subjects; an investor can select different subject elements according to his or her own preferences, risks, earnings and liquidity principle, and input selected elements into the product information calculation program of the system as a whole; and the information calculation program will outputs investment information for reference for the investor. With the Internet asset securitization resource integration system adopted, the enterprises can vitalize a large quantity of assets lack of liquidity, and therefore, the financial structure of the enterprises can be improved, and channels of fund sources can be broadened, and financing cost can be reduced.